2014
DOI: 10.1530/eje-13-0581
|View full text |Cite
|
Sign up to set email alerts
|

Six-year follow-up of a characteristic osteolytic lesion in a patient with tumor-induced osteomalacia

Abstract: Objective: Tumor-induced osteomalacia is a rare paraneoplastic syndrome characterized by hypophosphatemia and inappropriately normal or low 1,25-dihydroxyvitamin D. Clinical case: Here, we report a 6-year postoperative follow-up of a patient with oncogenic osteomalacia with a distinctive skeletal manifestation. The latter was characterized by an almost linear lytic lesion of a few millimeters with irregular borders, mainly involving the trabecular compartment but extending into cortical shell, located in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 15 publications
1
6
0
1
Order By: Relevance
“…Our data are in accordance with the low BMD and T ‐score in the two TIO patients described by Piemonte et al 11 and Malabanan et al 12 who also had low phosphorus and history of fractures at the time of diagnosis, with one of the patients using a wheelchair. Other studies that reported lower BMD in individuals with other causes of hypophosphatemic osteomalacia included vitamin D deficiency, nutritional malabsorption and renal tubular acidosis.…”
Section: Discussionsupporting
confidence: 92%
“…Our data are in accordance with the low BMD and T ‐score in the two TIO patients described by Piemonte et al 11 and Malabanan et al 12 who also had low phosphorus and history of fractures at the time of diagnosis, with one of the patients using a wheelchair. Other studies that reported lower BMD in individuals with other causes of hypophosphatemic osteomalacia included vitamin D deficiency, nutritional malabsorption and renal tubular acidosis.…”
Section: Discussionsupporting
confidence: 92%
“…To our knowledge, most publications about surgical excision of phosphaturic mesenchymal tumors have been case reports [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] , and very few were case series 2,33,34 . Phosphaturic mesenchymal tumors seem to be commonly located in long bones, but we are not aware of any studies comparing the results of curettage and segmental resection with a minimum one-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, calcium was abnormally high in ∼9% of the patients with pancreatic ductal adenocarcinoma and these patients could have a paraneoplastic syndrome. 20 In pancreatic cancer patients, the results of a systemic review have shown that dietary vitamin D or circulating concentrations of 25-hydroxyvitamin D are not associated with the risk of pancreatic cancer. 21 Other authors have found that, in men, there is an increased risk of pancreatic cancer associated with currently recommended dietary vitamin D intake levels; no associations with vitamin D intake were observed among women.…”
Section: Discussionmentioning
confidence: 99%